Activated carbon-coated cosmo ball biomedia for wastewater treatment - Shahot, Khaled Muftah (2017)
Current wastewater treatment systems, such as oxidation ponds, package systems, aerated lagoon, activated sludge, and various types of mechanical plants require long resident time to treat wastewater pollutants. With increasingly stringent discharge requirement, conventional WWTPs are no longer capable of producing effluent with the required quality. The aim of this study is to improve the surface of attached media in order to obtain a better removal efficiency in a biofilm reactor. Thus, the objectives of the study are to develop coating methods and characterize the coated surface to study the growth rate and mechanism of biofilm formation when a coated surface is used. This study also investigates the performance of activated carbon coated material with respect to organic and ammonia removal. In this research, various coating methods were attempted and the conditions of granular activated carbon (GAC) on high-density polypropylene (HDPE) were evaluated in the effort to enhance the surface area of the HDPE for application in wastewater treatment. In the biofilm study, a batch reactor with four AC coated Cosmo balls and four non-coated Cosmo balls were submerged in a 5-liter container filled with domestic wastewater. A laboratory-scale anoxic-aerobic reactor was installed at the Kolej 10 wastewater treatment plant and performance of the developed lab-scale reactor was evaluated under different conditions for coated and non-coated media. The results of the experiments showed that the granular activated carbon coating with particle diameter from 100 to 800 μm were successfully deposited on the HDPE substrates used. The coatings deposited on the HDPE substrate produced high surface roughness of around 7 μm which is 10 fold higher than non-coated media. The surface area of the coated substrate is higher compared to that of the non-coated substrate due the BET of activated carbon of 426 m2/g. The formation of biofilm was clearly observed after Day 11 to show that the biofilm had covered 100% of coated area as opposed to only an estimated 70% of the non-coated area. The highest removal of TP was achieved with coated Cosmo-Ball reactor which reached over 90% removal without the addition of any chemical, while only 54.6% TP was removed by the non-coated Cosmo-Ball. For organic removal, the coated Cosmo ball achieved 97.6% BOD, 92.2% COD and 98.3% TSS compared to non-coated Cosmo ball which gave 91% BOD, 87.8% COD and 92.47% TSS. Ammonia removal was significantly higher for coated Cosmo ball, 88.1% NH3-N contrast to non-coated 69.2% only. Two kinetic models namely Modified-Stover Kincannon and Grau were also studied to find kinetic parameters and the result showed that Modified-Stover Kincannon model can be recommended to be the best kinetic to use. The result of this research also showed that, after coating, there is four (4)-fold increase in the surface area of the media compared to the non-coated media. This had resulted in a significant decrease of HRT from 6 to 3 hours, and it could also save up to 50% of the volume of aeration tank.